V.P. Demikhov's monograph "Transplantation of vital organs In experiment" (1960) in foreign scientifi c press (to the 50th anniversary of the fi rst heart transplantation in human) - А. Werner; S. P. Glyantsev (Трансплантология (Москва), 2017)
.